Determining the average inbreeding coefficient in two ways using the example of the Gyimesi Racka - Kárpáti, Edina; Gáspárdy, András; Sáfár, László; Gulyás, László (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
The Gyimesi Racka is one of the Zackel-group variants bred in Transylvania. In the early 1990s it was re-introduced into Hungary (only in small numbers), then in the following years the national population of the breed increased due to some major imports of breeding animals. The stud book herd of the Gyimesi Racka ewes consists of almost 1000 individuals today. The authors estimated individual Wright’s inbreeding coefficient (COI) using Pedigree Viewer software based on the whole pedigree data (from 2005 to 2020). Mean inbreeding coefficients were also determined at baseline and transformed values. The average COI of the total herd book population (n=16947) was 1.99%, compared to the higher value of the subpopulation of inbred individuals (n=3828, 8.81%). As the number of maternal generations increased, the COI increased too significantly (P<0.001) in the total herd book population; in the eighth generation it was already 10.72%. On the other hand, in the subset of inbred individuals, the COI was more stagnant in the range of 8% and 10%, even though ANOVA confirms significant differences between generations. The corrected weighted mean and geometric mean obtained by log transformation took lower values (1.43% and 6.30%, respectively). We believe that the latter values are not only more favourable from the genetic diversity point of view, but also more reliable to characterize the mean of a group of animals, because they were obtained from a database that is closer to the normal distribution. However, based on the COI values calculated via both ways, the homozygosity status of today’s Gyimesi Racka stock is threateningly high, which draws attention to careful mating plan in the future.